2022
DOI: 10.1097/jpa.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Scholarly Activity of Authors of Research Articles Published in the Journal of Physician Assistant Education from 2011-2020

Abstract: Introduction The purpose of this study was to analyze bibliometric data and trends of author contributions to the Journal of Physician Assistant Education (JPAE) from 2011-2020. Methods Author data were collected from JPAE research articles published from 2011-2020. Publication history and h-index were obtained from Scopus. Data collected included first authors, last authors, and PA authors as well as trends in publications in JPAE. Descriptive statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Previous studies have reported a gender difference in scholarly productivity. 2,3 We found that men had more publications and scholarly activities, but the difference between men and women was not statistically significant. This was a secondary analysis of a larger study, and our sample was likely not large enough to find a significant difference if one truly exists.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous studies have reported a gender difference in scholarly productivity. 2,3 We found that men had more publications and scholarly activities, but the difference between men and women was not statistically significant. This was a secondary analysis of a larger study, and our sample was likely not large enough to find a significant difference if one truly exists.…”
Section: Discussionmentioning
confidence: 66%
“…Developing high-impact, highly visible researchers within our profession is important. Multiple barriers to PA research productivity have been suggested 2,3 ; a recent study found that lack of interest and lack of engagement with mentors by PA educators were underreported barriers. 4 Gender disparities in advancement in rank, representation in leadership, and salary are well-researched in other professions, [5][6][7] but nascent in the PA profession.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Later, Bouton and Halasy in a more recent analysis of bibliometric data of scholarly activity of authors of research articles in JPAE from 2011 to 2020 noted an increasing number of publications during this period for PA first and last authors, indicating increasing academic contribution by PA program faculty. 3 The Annual Survey of PA Programs, a yearly data profile of PA programs, was created in the 1980s by Dennis (Deni) Oliver, PhD, from the University of Iowa PA program. This report was the Association's first major research effort and provided important information as the field of PA education was rapidly growing.…”
Section: Introductionmentioning
confidence: 99%
“…2 Later, Bouton and Halasy in a more recent analysis of bibliometric data of scholarly activity of authors of research articles in JPAE from 2011 to 2020 noted an increasing number of publications during this period for PA first and last authors, indicating increasing academic contribution by PA program faculty. 3…”
Section: Introductionmentioning
confidence: 99%